Avoidable impacts of ocean warming on marine primary production: Insights from the CESM ensembles. Issue 1 (24th January 2017) - Krumhardt, Kristen M.; Lovenduski, Nicole S.; Long, Matthew C.; Lindsay, Keith
Abstract: As anthropogenic emissions and warming continue to alter Earth's environment, it is essential to highlight future impacts that can be avoided through mitigation. Here we use two ensembles of the Community Earth System Model (CESM) run under the business‐as‐usual scenario, RCP 8.5, and the mitigation scenario, RCP 4.5, to identify avoidable impacts of anthropogenic warming on marine net primary production (NPP). We emphasize the use of ensembles so as to distinguish long‐term, anthropogenic trends in marine productivity from internal variability. Twentieth century globally integrated marine NPP is 55.7 ± 1 Pg C, with much of the variability attributable to certain regions (e.g., the equatorial Pacific). CESM projections indicate that global marine NPP will drop by ∼4% by 2080 if we follow RCP 8.5, but only by 2% under RCP 4.5. The response to warming on a global scale includes compensating regional effects; NPP increases in polar and eastern equatorial Pacific waters but decreases in the Atlantic, western Pacific, and Indian Oceans. The two main phytoplankton groups simulated in CESM show distinct responses: diatoms decrease their NPP, while small phytoplankton NPP increases over the mid‐21st century. Trends in NPP from mid‐21st century to 2080 are significantly different between the two emission scenarios mainly in the Atlantic Ocean basin and therefore impacts here are "avoidable" if we follow RCP 4.5, rather than RCP 8.5. In contrast, changes in NPP on a global scale and in most areas of the Pacific and Indian basins and the Southern Ocean are not distinguishable between forcing scenarios. Key Points: Climate warming during the 21st century results in reduced marine net primary production on a global scale Ensemble simulations allow for an investigation of ensemble mean trends across two emission scenarios in the presence of natural variability Significant decreases in marine net primary production in the Atlantic basin may be avoided with a mitigation emission scenario